Na selva de pedras: as performances de gênero e sexualidade nos conflitos entre prostituição, crime e Estado - Mello, Breno Marques de (2019)
Prostitution and the illicit drug market are in a blurred zone in Brazilian legislation. It is not currently possible to understand the legal criteria used to criminalize sex workers, those who are sexually exploited and those who benefit from the financial gains of sex workers. In Brazil, being a prostitute is not a crime. However, the whole environment of this activity is typified in the Penal Code. Like prostitution, laws and lawsuits do not have precise elements that indicate what conditions someone can be considered a "drug user" or " drug dealer." The narratives found during the research showed that over the years prostitutes and the subjects of the illicit drug market have developed approximations, whose the legal ambiguities have participated and facilitated several conflicts. However, the consumption and sale of drugs, especially crack, have produced significant clashes between sex workers, illicit drug market participants, and the State. In this way, the sex workers began to divide themselves between prostitutes and “noiadas”, after the beginning of these clashes. The intersections between these conflicts have dynamics activated by conventions of gender, sexuality, race and class. The subjects involved tell their stories and manage the narratives indicating that the processes of proximity have been crossed by practices of violence that have the State and other subjects as protagonists. The clashes between these two fields, therefore, occupy the center of the analyzes. The object of the research is about the performances, in gender and sexuality, that occur in the conflicts between prostitution, the illicit drug market and the State, from the narratives found in the prostitution zones in João Pessoa. The methodology of the work prioritized the ethnographic work and the in-depth interviews with the sex workers.